CRIMINAL LIABILITY FOR MALPRACTICE OF DOCTORS AT PEKAN BARU HOSPITAL, RIAU PROVINCE - Yudi Krismen; Satrio Abdillah (Universitas Padjadjaran, 2023)
The primary purposes of this research are to investigate the multifaceted role of health workers in the delivery of health services and to explore the legal aspects surrounding medical malpractice within the healthcare system. Specifically, this study aims to examine the evolving perception of health workers in society, moving beyond their traditional role as “healers” to encompass their broader responsibilities. Additionally, it seeks to understand the legal implications of medical errors and malpractice within the healthcare system, with a focus on negligence as a central factor. The issue of malpractice, because of the legal awareness of patients who feel aggrieved, results in the prosecution of doctors who commit medical errors (malpractice) which end up in criminal prosecution of patients who feel aggrieved, it is realized by all parties that doctors are only human beings who can one day be negligent and make mistakes, so that violations of the code of ethics can occur even to the point of violating applicable health regulations.This study employes a normative legal research approach to comprehensively examine the multifaceted role of health workers and the intricate legal dimensions surrounding medical malpractice within the healthcare sector. The result of the study found hospital criminal liability for malpractice committed by the hospital or by its health workers can be based on the doctrines of vicarious liability, hospital liability, and strict liability. Doctor’s medical malpractice in medical services can be intentional or negligent. What can be accounted for in medical malpractice is only a doctor’s negligence in carrying out medical procedures.